Ribosomal protein L11- and retinol dehydrogenase 11-induced erythroid proliferation without erythropoietin in UT-7/Epo erythroleukemic cells - Tanawan Kummalue (2018)
© 2015 ISEH - International Society for Experimental Hematology. Erythropoiesis is the process of proliferation, differentiation, and maturation of erythroid cells. Understanding these steps will help to elucidate the basis of specific diseases associated with abnormal production of red blood cells. In this study, we continued our efforts to identify genes involved in erythroid proliferation. Lentivirally transduced UT-7/Epo erythroleukemic cells expressing ribosomal protein L11 (RPL11) or retinol dehydrogenase 11 (RDH11) could proliferate in the absence of erythropoietin, and their cell-cycle profiles revealed G0/G1 prolongation and low percentages of apoptosis. RPL11-expressing cells proliferated more rapidly than the RDH11-expressing cells. The antiapoptotic proteins BCL-XL and BCL-2 were expressed in both cell lines. Unlike the parental UT-7/Epo cells, the expression of hemoglobins (Hbs) in the transduced cells had switched from adult to fetal type. Several signal transduction pathways, including STAT5, were highly activated in transduced cells; furthermore, expression of the downstream target genes of STAT5, such as CCND1, was upregulated in the transduced cells. Taken together, the data indicate that RPL11 and RDH11 accelerate erythroid cell proliferation by upregulating the STAT5 signaling pathway with phosphorylation of Lyn and cyclic AMP response element-binding protein (CREB).